Towards the Effect of Acoustic Emission (AE) Sensor Positioning within AE Signal Parameters in Sliding on Bulk Ultrafine-Grained Materials; AIP Conference Proceedings; Vol. 1909 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2017 (AMHS’17) - Filippov A. V. Andrey Vladimirovich; Tarasov S. Yu. Sergei Yulievich; Podgornykh O. A. Oleg Anatolievich; Chazov P. A. Pavel Andreevich; Shamarin N. N. Nikolay Nikolaevich; Filippova E. O. Ekaterina Olegovna (2017, 2017)
Title screen